The Existence of Personality and Hikikomori State: a Socio-Philosophical Reflection on the Consequences of the COVID-19 Pandemic - Olena Honcharova; Olga Kyvliuk; Inna Chugueva (Studia Warmińskie, 2022)
The article is devoted to the problem of humans joining the ranks of hikikomori at the time of and after the introduction of strict quarantine measures during the COVID-19 pandemic. The lifestyle of the hikikomori, as a specific subcultural trend that focuses on the physical distancing of the individual from the space of social communication, is emphasised. During the COVID-19 pandemic, the hikikomori lifestyle became common to many people under a regime of enforced self-isolation. However, even when quarantine measures are relaxed and a return to familiar communication practices is allowed, not all people are willing to return to offline life. Attitudes towards temporality also change under conditions of pandemic and enforced self-isolation, where complex ethico-social dilemmas arise, bringing psychological discomfort to the individual on micro-and macro levels.